Perbandingan Luaran Klinis Pasien Stroke Iskemik dengan Hipertensi dan Non Hipertensi di UPT RSUD Undata Provinsi Sulawesi Tengah Periode Maret 20202 – Maret 2022 - Tsurayya Fadilah Ramadhani; Fitriah Handayani; Ria Sulistiana; Gabriella Bamba Ratih Lintin (Yayasan Literasi Sains Indonesia, 2022)
Stroke is the main cause of disability at high risk for cognitive impairment. Hypertension is the main trigger for the occurrence of stroke. The Barthel Index is one of the measuring tools used to assess patients with neurological disorders and undergoing rehabilitation. This study aims to compare the clinical outcomes of ischemic stroke patients with hypertension and non-hypertension at Undata Hospital of Central Sulawesi Province from March 2020 to March 2022. This study uses an analytical observational research method with a cross-sectional design. The samples consist of 68 patients. The data were collected through secondary data, namely medical records of ischemic stroke patients with hypertension and non-hypertensive. The data were tested for normality using the Kolmogorov-Smirnov test and processed using the Mann-Whitney and the unpaired T-tests. The results show no comparison of clinical outcomes of ischemic stroke patients with hypertension and non-hypertension. The results of statistical tests of the Barthel index before going to the hospital obtained a p-value of 0.106. and the results of statistical tests of the Barthel index after hospitalization is a p-value of 0.881. There is no difference in clinical outcomes in ischemic stroke patients with hypertension and non-hypertension at Undata Hospital of Central Sulawesi Province from March 2020 to March 2022.